Research on Mixed Data Rate in WDM Networks - Li Li; Chu Ze-nan; Dong Zhao (Institute of Advanced Engineering and Science, 2013)
To meet the growing data traffic demands in the telecommunication applications, the number of wavelengths is to be increased in a fiber-optic backbone of the telecommunication network. The exponential growth of internet services, transmission capacity is a tremendous challenge to networks. Nowadays, 10 Gbps transmission systems are being used for commercial applications. At the same time, the non-linear effects such as FWM, SRS, XPM, SPM, and Dispersion are also increased, when the number of wavelengths passing through the single fiber is increased. The analysis of efficient modulation formats for DWDM system and long-haul transmission system, we go for various modulations for DWDM system. The maimum data rate for NRZ-OOK modulation format is 10 Gbps. For RZ-OOK the maximum rate is 50 Gbps. Since RZ-OOK modulation uses twice the band width when compared to NRZ-OOK modulation. The modulation format is partially upgraded from OOK to PSK, the influence of OOK signals on the updated PSK signals must be considered when using multi-channel wavelength conversion. The PSK modulation is also analyzed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.2515